Algae An Introduction to Phycology - Hoek, Christiaan Van Den Mann, D.G (Cambridge University Press, 1955)
"Algae are ubiquitous. A multitude of species, ranging from microscopic unicells to gigantic kelps, inhabit the world's oceans, freshwaters, soils, rocks and trees. To understand the basic role of algae in the global ecosystem, a reliable and modern introduction to their kaleidoscopic diversity, systematics and phylogeny is indispensable. This volume provides such an introduction." "The text represents a completely revised and updated edition of a highly acclaimed German textbook, which was heralded for its clarity as well as its breadth and depth of information. This new edition takes into account recent re-evaluations in algal systematics and phylogeny that have been made necessary by insights provided by the powerful techniques of molecular genetics and electron microscopy, as well as more traditional life history studies." "Each main algal group is considered in turn, its principal characteristics outlined and its ecological peculiarities and phylogenetic relationships discussed, to provide a unique and comprehensive survey of this fascinating group of plants. A final chapter summarizes the phylogeny of algae in relation to other phyla." "This book provides a wealth of information for all those studying or working with algae. A full glossary and comprehensive list of references are two additional features that will make this book an indispensable source of reference for many years to come."-